TRANSFORMASI DATA PADA SERTIPIKAT TANAH: ANALISIS PERBANDINGAN ANTARA SERTIPIKAT ELEKTRONIK DAN ANALOG: Data Transformation On Land Certificates:A Comparative Analysis Of Electronic And Analog Certificates - Nadhirah Baisa; Ignatius Pradipa Probondaru (Reformasi Hukum Trisakti, 2025)
The transformation of technological advancements and the existence of digitalization has created a shift in the land registration system from paper-based to electronic, this shift has given birth to a new product, namely an electronic certificate that is different from the previous certificate, namely an analog certificate. The formulation of the problem is how the features in presenting data differ between electronic certificates and analog certificates. The research method, the type of normative legal research is descriptive with secondary data, namely laws and regulations, and related journals, analyzed qualitatively and deductively drawing conclusions. The results of the discussion and conclusions are the differences in data presentation features between analog and electronic certificates including document forms, increased security features with editions, the use of electronic signatures, and simplification of substance with QR codes, electronic certificates do have a minimal risk of loss and damage due to natural disasters because of supporting features that previously did not exist in analog. However, many still do not know the differences in data presentation features between the two, one of which is the QR Code that can be scanned on the Touch Tanahku application.